Pengaruh Pendidikan, Status Perkawinan dan Kesehatan Terhadap Partisipasi Kerja Penduduk Lansia Wanita di Sumatera Barat - Putri Kurnia; Ariusni Anis (Universitas Negeri Padang, 2020)
This study aims to analyze: (1) The effect of the level of education on the work participation of elderly women in West Sumatra. (2) Effect of marital status on work participation of elderly women in West Sumatra. (3) Effect of health conditions on the work participation of elderly women in West Sumatra. This type of research is descriptive and associative research. The data used is the National Socio-Economic Survey (SUSENAS) in 2018. The method uses Logistic Regression Analysis. The results of the study are: (1) the level of education has a significant negative effect on the work participation of elderly women in West Sumatra. (2) Marital status has a significant negative effect on the work participation of elderly women in West Sumatra. (3) Health conditions have a significant positive effect on the work participation of elderly women in West Sumatra.